First person - Manh Tin Ho and Jiongming Lu (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Manh Tin Ho and Jiongming Lu are co-first authors on 'A translation-independent activity of PheRS activates growth and proliferation in Drosophila', published in DMM. Manh Tin conducted the research described in this article while a PhD student in the lab of Beat Suter at the University of Bern, Bern, Switzerland, and is now a postdoctoral researcher in the lab of Daniel Fuster at the University of Bern, investigating kidney disease and sodium/proton exchange membrane proteins. Jiongming conducted the research described in this article while a PhD student in the lab of Beat Suter at the University of Bern, and is now a postdoctoral researcher in the lab of Linda Partridge at the Max Planck Institute for Biology of Ageing, Köln, Germany, investigating molecular mechanisms and new strategies of healthy ageing.